Synthesis and Characterization of Some Novel N-Phenylpyrazole Analogues for the Evaluation of their Potentials as Anticancer, Antimicrobial and Antioxidant Agents - Pothuri, Vijai Varma; Palagummi, Venkata Satya Machiraju; Vasa, Samba Siva Rao (Indian Journal of Pharmaceutical Education and Research, 2020)
Objectives: With a view to invent new anticancer agents, the authors proposed to prepare a series of N-phenylpyrazole derivatives by introducing biologically active pharmacophores viz., Fluoro/Fluoromehtyl benzamide and 2, 3-dihydrobenzo[b][1,4] dioxin at 3-, 5- positions of N-phenyl pyrazole motif respectively. Methods: The newly formed products are characterized by 1H NMR, 13C NMR, Mass and FTIR spectroscopic techniques and are subjected to screened for anticancer activity against human liver cancer cell line (Hep G2), antimicrobial and antioxidant activities. Further, Molecular docking study has also been applied on the newly synthesized compounds to study the binding efficiencies with protein BCL2 using GOLD docking software. Results: Among all the newly synthesized compounds, three compounds 8(d), 8(e), 8(h) exhibited higher potentials of anticancer activity compared to the rest of the compounds. All the newly synthesized compounds exhibited antimicrobial and antioxidant activities. Further study of molecular docking with protein BCL2 revealed that three title compounds 7, 8(f) and 8(h) exhibited very good binding efficiencies.
Keywords: Anticancer; BCL2; Chalcone; Hep G2; Molecular docking; Pyrazole